Partial purification and properties of cyclodextrin glycosiltransferase (CGTase) from alkalophilic Bacillus species - Mora, Marlene M Martínez (Springer International Publishing AG, 2012)
Cyclodextrin glucanotransferase (CGTase, EC 2.4.1.9) is an unique enzyme capable of converting starch and related substrates into cyclodextrins (CDs). In this paper, we report an one step gel purification method of CGTase from Bacillus sp. and later enzyme characterization. The Bacillus sp. strain was isolated from a Colocacia esculenta rizospheric soil sample and the CGTase production was carried out in alkaline medium (pH=10). The CGTase purification from the culture supernatant was performed by gel filtration. The enzyme was purified in one step with a recovery of 87.3% activity and 40-fold purification for specific enzymatic activity of 2.24 U/mg. Optimal activity was observed at pH 5.0 in citrate-phosphate buffer, and the enzyme retained almost 100 % of its activity between pH 5.5 and 10 after incubation for 1 h at 4°C. The enzyme exhibited maximum activity at 55°C and showed a T(50%) of 70°C. The ratio of α:β:γ CD formed by the enzyme was 0.74:1:0.61 for soluble starch and 0.29:1:0.85 for cocoyam starch.